Analysis of factors influencing college students’ food waste behavior and evaluation of labor education intervention - Wang, Dandan; Zhang, Kaiyue; Lv, Xin; Xue, Liang; Yang, Zhenyu; Li, Peng (Frontiers in Public Health, 2024)
Background Food waste remains a major problem for the world and food security. Despite the fact that consumers are significant producers of food waste, little research attention has been paid to college students. The present study aimed to assess food waste and the influence factors among college students. Additionally, the goal was to improve college students’ food waste attitudes and behaviors through labor education. Methods Through an online questionnaire survey, 407 college students from three universities were asked about food waste; 27 students of them were randomly selected as the research object, and labor practice was carried out in groups in the student cafeteria. Mann–Whitney U test was performed to show food waste behavior of college students and logistical regression analysis was used to analyze the factors affecting food waste behavior. Results The results indicated that the food waste is more serious among college students in East China, senior or female students, BMI plays a positive role in food waste among college students, while monthly consumption and peers waste play a negative role in food waste. After participating in the labor education, the students’ views and practices toward their peer’s food waste have improved. Conclusion The implementation of labor education in college canteens is conducive to the establishment of a correct outlook on labor as well as saving consciousness among college students, and to the formation of a social consciousness of saving.